Enzymatic hydrolysis for methane production from hydrolysate food waste - Deb, Nibedita; Alam, Md Zahangir; Rahman, Tawfkur; Jami, Mohammed Saedi; Mansor, Mariatul Fadzillah Bt (Chemical Engineering Research Bulletin, 2026)
The study aimed to assess how different pretreatment methods affect the enzymatic breakdown of carbohydrate-rich food waste, including cellulose, glucose, starch, lignin, and hemicellulose. The goal was to use these sugars effectively to reduce methane production costs. Using kinetic modelling, the study tested various pretreatment techniques, intending to promote the economical use of waste materials in microbial fermentations, thus reducing production expenses. The findings aimed to support waste material utilization for cost reduction. Anaerobic digestion experiments were conducted using sewage sludge under stable conditions (pH 7, 30°C) for 28 days. Samples were untreated or treated with hydrolytic enzymes. After 5 days, both groups exhibited reducing sugar concentrations. The untreated group had the highest rate of production (23 day-1), while the lowest was in samples treated with 50% cellulose and 50% amylase (28 day-1). The study found that excluding nutrients substantially enhanced biogas concentrations, suggesting that using food waste without added nutrients and a 5-day hydrolysis could significantly cut production costs. However, further optimization is necessary for higher yields. Chemical Engineering Research Bulletin: 24 (Issue 1): 113-128